Post-truth, denialism and fake news: Introductory essay - Ianni Segatto, Antonio (2023)
This brief introduction to the dossier presents the phenomena of post-truth, denialism and fake news based on three questions. The first is “What is the truth of post-truth?”. The answer is that post-truth does not constitute a new kind of truth, but a way of discrediting the way truth is justified. The second question is “What does denialism deny?”. The suggested answer points out that scientific denialism, in particular, denies not only scientific theses, but above all the scientific investigation procedures themselves. The third question is “What is false in fake news?”. The answer aims to show that the falsity of fake news lies in its ideological character.